The relationship between bone mineral density and hematological parameters in the geriatric age group - Önalan, Erhan; Gökalp, Yusuf (My University, 2020)
Introduction: As populations gradually become older, osteoporosis manifests itself as an important public health problem. Studies have shown that inflammation plays a critical role in the pathogenesis of osteoporosis. NLR (neutrophil to lymphocyte ratio) and PLR (platelet to lymphocyte ratio) are simple, non-invasive, and inexpensive markers of inflammation in malignancies and inflammatory diseases. This study aims to compare osteopenic, osteoporotic, and control subjects, who do not have other known diseases or a history of medication use, in terms of their NLR and PLR levels and evaluate the relationship between NLR, PLR levels and BMD. Methods: This cross-sectional study included a total of 308 patients aged 65 or above. Total bone mineral density (BMD) was measured using dual energy X-ray absorptiometry (DEXA). Complete blood count (CBC), biomarkers of inflammation (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), glucose/lipid metabolism, and thyroid function test results were recorded. Results: The osteoporosis group demonstrated higher NLR levels compared to the osteopenic and control groups (respectively 3.58 ± 4.22, 2.64 ± 1.99, and 2.36 ± 1.39), and this relationship between the groups was found to be statistically significant (p=0.025). Our data revealed higher sedimentation values for the osteoporosis group than for the osteopenic and healthy control groups with statistical significance (p=0.011). Conclusions: The fact that individuals with geriatric osteoporosis demonstrate elevated NLR levels and that this elevation is also seen in sedimentation suggests that inflammation plays an important role in bone remodelling.
Keywords: Genel ve Dahili Tıp; Patoloji; Geriatri ve Gerontoloji; Onkoloji; Sağlık Bilimleri ve Hizmetleri; Ortopedi